Regulation of gene expression via retrotransposon insertions and the noncoding RNA 4.5S RNAH. (3rd September 2015) - Ishida, Kentaro; Miyauchi, Kenjyo; Kimura, Yuko; Mito, Mari; Okada, Shunpei; Suzuki, Tsutomu; Nakagawa, Shinichi
Abstract : Short interspersed elements (SINEs) comprise a significant portion of mammalian genomes and regulate gene expression through a variety of mechanisms. Here, we show that Myodonta clade‐specific 4.5S RNAH (4.5SH), an abundant nuclear noncoding RNA that is highly homologous to the retrotransposon SINE B1, controls the expression of reporter gene that contains the antisense insertion of SINE B1 via nuclear retention. The depletion of endogenous 4.5SH with antisense oligonucleotides neutralizes the nuclear retention and changes the subcellular distribution of the reporter transcripts containing the antisense SINE B1 insertion. Importantly, endogenous transcripts with antisense SINE B1 were increased in the cytoplasm after knockdown of 4.5SH, leading to a decrease in cellular growth. We propose a tentative hypothesis that the amplification of the 4.5SH cluster in specific rodent species might delineate their evolutionary direction via the regulation of genes containing the antisense insertion of SINE B1. Abstract : mRNAs containing antisense insertions of SINE B1 are partially retained in the nucleus via a species‐specific short ncRNA 4.5SH.